Hippocampus at 25. Issue 10 (29th July 2016) - Eichenbaum, Howard; Amaral, David G.; Buffalo, Elizabeth A.; Buzsáki, György; Cohen, Neal; Davachi, Lila; Frank, Loren; Heckers, Stephan; Morris, Richard G. M.; Moser, Edvard I.; Nadel, Lynn; O'Keefe, John; et al.
Abstract : ABSTRACT The journal Hippocampus has passed the milestone of 25 years of publications on the topic of a highly studied brain structure, and its closely associated brain areas. In a recent celebration of this event, a Boston memory group invited 16 speakers to address the question of progress in understanding the hippocampus that has been achieved. Here we present a summary of these talks organized as progress on four main themes: (1) Understanding the hippocampus in terms of its interactions with multiple cortical areas within the medial temporal lobe memory system, (2) understanding the relationship between memory and spatial information processing functions of the hippocampal region, (3) understanding the role of temporal organization in spatial and memory processing by the hippocampus, and (4) understanding how the hippocampus integrates related events into networks of memories. © 2016 Wiley Periodicals, Inc.